2023
DOI: 10.1101/2023.10.07.561338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomolecular condensates form spatially inhomogeneous network fluids

Furqan Dar,
Samuel R. Cohen,
Diana M. Mitrea
et al.

Abstract: The functions of biomolecular condensates are thought to be influenced by their material properties, and these are in turn determined by the multiscale structural features within condensates. However, structural characterizations of condensates are challenging, and hence rarely reported. Here, we deploy a combination of small angle neutron scattering, fluorescence recovery after photobleaching, and bespoke coarse-grained molecular dynamics simulations to provide structural descriptions of model condensates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…A machine-learning-based approach, CAMELOT, 181 has been developed to optimize the parameters of coarsegrained models, and it was recently applied to a binary phase separation system to explain the structural features of condensates. 182 Off-lattice phase separation simulations often involve the implementation of slab methods, which utilize spatially limited simulation boxes with a non-periodic-boundary condition. 167,173 Typically, a simulation box adapts a cuboid shape with one significantly long axis (z-axis); the xz and yz boundary planes are periodic, but the xy boundary planes are nonperiodic.…”
Section: Off-lattice Modelsmentioning
confidence: 99%
“…A machine-learning-based approach, CAMELOT, 181 has been developed to optimize the parameters of coarsegrained models, and it was recently applied to a binary phase separation system to explain the structural features of condensates. 182 Off-lattice phase separation simulations often involve the implementation of slab methods, which utilize spatially limited simulation boxes with a non-periodic-boundary condition. 167,173 Typically, a simulation box adapts a cuboid shape with one significantly long axis (z-axis); the xz and yz boundary planes are periodic, but the xy boundary planes are nonperiodic.…”
Section: Off-lattice Modelsmentioning
confidence: 99%
“…Source data are provided as a Source Data file with this manuscript and via the GitHub repository of the Pappu lab https://github.com/ Pappulab/n130-liquid-structure/. Input files for the simulations and coordinate files of the final outputs are available via Zenodo at https:// zenodo.org/doi/10.5281/zenodo.10823199 131 . PDB 4N8M is available from the Protein Data Bank.…”
Section: Reporting Summarymentioning
confidence: 99%
“…A recent study showed that RNAs have an intrinsic propensity to undergo protein-free phase separation in vitro upon heating with lower critical solution temperatures (LCSTs), driven by desolvation entropy and Mg 2+ -dependent physical cross-linking of RNA molecules 45 . The thermo-responsive phase separation of RNAs can be coupled to an intra-condensate networking transition within the dense phase, referred to as percolation 46, 47, 48 , which engenders long-lived physical cross-linking of RNA chains through nucleobase-specific interactions. Importantly, phase separation and percolation of RNA chains are two distinct transitions, the former being an entropy-driven density transition leading to the formation of phase-separated RNA condensates and the latter being an associative transition mediated by multivalent RNA-RNA interactions.…”
Section: Introductionmentioning
confidence: 99%